The effect of anesthesia technique on tumor reccurrence rate after mastectomy - Dulgeroglu, Melis; Firat, Aynur Camkiran; Araz, Coskun; Candan, Selim (International Journal of Research in Medical Sciences, 2020)
Background: Breast cancer is most common cancer in women. Although surgical and chemotherapy methods have improved survival, mortality is seen secondary to metastasis and recurrence. Neuroaxial anesthesia has been shown to suppress neuroendocrine stress response due to surgery with sympathetic blockade and has a positive effect on tumor recurrence. In this study, the hypothesis was regional anesthesia may have a positive effect on patient comfort, surgical success rate and complications in the short term, tumor recurrence and metastasis in the long term. Methods: Patients who underwent mastectomy for breast cancer were divided into two groups as thoracic epidural or general anesthesia retrospectively. Preoperative patient characteristics, intraoperative hemodynamic data and postoperative complications were recorded. Static and dynamic pain was evaluated at 12, 24 and 48 hours, at 1 week, 3 and 6 months, and at the end of 1 and 3 years. The presence of metastasis and recurrence was evaluated. Results: In this study, no relationship between recurrence and anesthesia type (p=1.0) could be found. Intraoperative hemodynamic data and pain scores were lower in patients who underwent thoracic epidural anesthesia. Conclusions: As a result, thoracic epidural anesthesia had hemodynamic effects and lower pain scores in postoperative pain control, but had no effect on tumor recurrence in breast cancer patients.